User acceptance of free open source integrated library management systems (FOS-ILMS) in selected academic libraries in Metro Manila - Carlos, Azenith F. (2012)
Librarians , now more than ever, are in a significant position to acquire and modify Free and Open Source Software (FOSS) Integrated Library Management System (ILMS) without paying royalties. With the proliferation of different FOSS ILMS, how are the Academic Libraries in Metro Manila Manila responding?